Performance Assessment of an Existing Reinforced Cement Concrete T-Beam and Slab Bridge Using Pushover Analysis - Umarani Gunasekaran; oseenid Teresa Amaladosson; Premavathi Narayanan; Kanchanadevi Ashokkumar (The Baltic Journal of Road and Bridge Engineering, 2013)
The objective of this paper is to evaluate the structural condition of an existing reinforced cement concrete T-beam and slab bridge and to check its survivability under two imposed ground motions. A three dimensional finite element model of the bridge was developed using Structural Analysis and Program Software SAP2000. The finite element model of the bridge was subjected to ground motions along the transverse and longitudinal directions. A nonlinear static pushover analysis was carried out and the capacity curves were obtained. The seismic demands and the capacities were established. The performance of the bridge was assessed and the results are reported.